PROBLEMATIKA KEBIJAKAN PENGARUSUTAMAAN GENDER DALAM MENGATASI MARJINALISASI PEREMPUAN - Santoso, Widjajanti M (P2KK LIPI, 2014)
As shown from the gap between actual situation of gender inequity and the implementation of gender policy, it can be seen that the representation of gender policy is low. Gender mainstreaming is a knowledge as well as a strategy to build gender equality. The sensitivity of gender issue has been acknowledged by international community commitment through several international meetings, that this issue must be integrated into national policy. Although Indonesia has ratified The Convention on the Elimination of All Forms of Discrimination against Women (CEDAW) into the UU No. 7 year 1984, the Gender Mainstreaming policy has only implemented in 2000 with the Inpres No 9. The gap between Human Development Index and Gender Development Index, despite the increase of both indexes, also shows that the problem of marginalization of women is still exist in Indonesia. The data from the indexes also show that Indonesia is unable to fulfill the MDG’s goal in preventing the number of death of mother in delivering baby. As strategy, the Gender Mainstreaming shows challenges from individual as well as bureaucracy, not to mention problem in ideas, interest and institution that tend to exclude gender as priority. The exsternal challenges are capitalism through media that sometimes have differentinterest. As strategy gender mainstreaming needs media to disseminate gender problem and gender knowledge. Keywords: gender mainstreaming, representation, women’s knowledge, strategy, policy